2020
DOI: 10.1128/msphere.00994-20
|View full text |Cite
|
Sign up to set email alerts
|

Unique Mode of Cell Division by the Mycobacterial Genetic Resister Clones Emerging De Novo from the Antibiotic-Surviving Population

Abstract: The emergence of antibiotic genetic resisters of pathogenic bacteria poses a major public health challenge. The mechanism by which bacterial antibiotic genetic resister clones formed de novo multiply and establish a resister population remained unknown. Here, we delineated the unique mode of cell division of the antibiotic genetic resisters of Mycobacterium smegmatis and Mycobacterium tuberculosis formed de novo from the population surviving in the presence of bactericidal concentrations of rifampicin or moxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…The CFU scores, from the plates with and without rifampicin, overlapped consistently from the 39 hr and 48 hr of exposure of arr -KO and WT cultures, respectively (n = 3 biological replicates in each case). The overlapping showed that the regrowing cells would all have originated from rifampicin-resistant clones, divided using unusual cell division mechanisms and grown, as reported by us recently ( Jakkala et al., 2020 ). Despite both the cultures behaving in a similar manner, the mass doubling time of arr- KO from 39 hr onwards was 4.10 hrs and that of WT from 48 hr onwards was 5.25 hrs (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The CFU scores, from the plates with and without rifampicin, overlapped consistently from the 39 hr and 48 hr of exposure of arr -KO and WT cultures, respectively (n = 3 biological replicates in each case). The overlapping showed that the regrowing cells would all have originated from rifampicin-resistant clones, divided using unusual cell division mechanisms and grown, as reported by us recently ( Jakkala et al., 2020 ). Despite both the cultures behaving in a similar manner, the mass doubling time of arr- KO from 39 hr onwards was 4.10 hrs and that of WT from 48 hr onwards was 5.25 hrs (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Fourthly, there was no possibility of hypoxia setting in in the well aerated cultures with 170 rpm shaking. Further, when the cells in the rifampicin surviving population gained rpoB mutation, they regrew to establish a rifampicin-resistant population, as reported by us ( Jakkala et al., 2020 ). Thus, taken together, the data suggested very low probability of adaptation of the arr -KO cultures to hypoxia under the culture conditions used in the study.…”
Section: Discussionsupporting
confidence: 60%
“…Environmental stresses such as hypoxia, nutrient deprivation, and host immune effectors can generate genome-wide mutations in subsets of cells, leading to heritable genetic resistance ( Sebastian et al., 2017 ; Ragheb et al., 2019 ; Hicks et al., 2020 ; Jakkala et al., 2020 ; Swaminath et al., 2020 ). The activity and efficiency of different DNA repair pathways influences the rate at which these cells are a reservoir from which resistant isolates emerge.…”
Section: The Updated Model: Tolerance On the Pathway To Resistancementioning
confidence: 99%
“…SCs were found to be more susceptible than NCs to antibiotics (rifampin and isoniazid), H 2 O 2 , and acidified NaNO 2 . Additionally, drug resistant bacteria display a distinct mode of cell division and cell length heterogeneity when compared with drug sensitive bacteria ( Vijay et al., 2017b ; Jakkala et al., 2020 ). Notably, mycobacteria exhibit a unique kind of heterogeneity under stress where it asymmetrically distributes irreversibly oxidized proteins within bacteria and between their progeny ( Vaubourgeix et al., 2015 ).…”
Section: Mechanisms Underlying Heterogeneity In Culturabilitymentioning
confidence: 99%